DESENVOLVIMENTO DO PROJETO CONCEITUAL DO VEICULO DE COMPETIÇÃO OFF - BONFADA, ANDERSON R.; VALDIERO, ANTONIO C.; KAFFKA, DAVID; GILAPA, GENARO M. M.; STAMM, JOAO G.; HEIMBURG, JULIO C. V.; DANETTE, LUCAS I.; BATAGLIN, MARCELO; BENATTI, MATEUS; DECIAN, MAXUEL R. B.; et al. (Salão do Conhecimento, 2013)
Resumo